A Review of Tofacitinib in the Treatment of Rheumatoid Arthritis and Psoriasis. Issue 4 (December 2014) - Fanucci, Kristina A.; Rosmarin, David M.; Gottlieb, Alice B.
Tofacitinib is a novel Janus kinase (JAK) inhibitor. JAKs activate immune cells and pro-inflammatory cytokines. Thus, they are critical in the pathogenesis of many diseases including autoimmune diseases such as rheumatoid arthritis (RA) and psoriasis. Existing treatments for RA and psoriasis do not provide all patients with sufficient disease control. Furthermore, some patients develop resistance or have adverse events to current therapies. Patients whose disease is not controlled appropriately by available treatments highlight the need for drugs with novel targets, convenient administration routes, continued efficacy, and long-term tolerability. Tofacitinib can be administered orally or topically and has been shown to be an effective treatment for RA and psoriasis. This article reviews the mechanism of action, pharmacodynamics, pharmacokinetics, and metabolism of tofacitinib and discusses the clinical trials conducted to show the efficacy and safety of oral tofacitinib in the treatment of RA and oral and topical tofacitinib in the treatment of psoriasis.